2020
DOI: 10.1111/jcmm.15861
|View full text |Cite
|
Sign up to set email alerts
|

A circulating exosomal microRNA panel as a novel biomarker for monitoring post‐transplant renal graft function

Abstract: Since the first successful kidney transplant in 1954, kidney transplantation has become the routine management for patients presenting with end-stage renal disease. 1 The application of highly effective immunosuppressive drugs over the past 20 years has significantly improved the 1-year survival of kidney grafts. 2 However, chronic allograft dysfunction, which may due to both immunologic and non-immunologic factors, is the major cause of renal allograft loss in the long-term. 3,4 Thus, accurate assessment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…44 More recently, it has been suggested that proteomic analysis of circulating EVs in kidney transplant recipients might discriminate grafts with poor outcomes, 45 whereas Chen et al identified an exosomal miRNA panel (miR-21-5p, miR-210-3p, and miR-4639-5p) as a potential biomarker of chronic allograft dysfunction. 46 Assessment of kidney allograft rejection. Immune monitoring of kidney transplants and development of noninvasive biomarkers of immune-mediated injury is an unmet need in kidney transplantation.…”
Section: Q8mentioning
confidence: 99%
“…44 More recently, it has been suggested that proteomic analysis of circulating EVs in kidney transplant recipients might discriminate grafts with poor outcomes, 45 whereas Chen et al identified an exosomal miRNA panel (miR-21-5p, miR-210-3p, and miR-4639-5p) as a potential biomarker of chronic allograft dysfunction. 46 Assessment of kidney allograft rejection. Immune monitoring of kidney transplants and development of noninvasive biomarkers of immune-mediated injury is an unmet need in kidney transplantation.…”
Section: Q8mentioning
confidence: 99%
“…Based on the emerging data from other scientific fields, it is expected that exosomal miRNA profiling could be a non-invasive method to detect disease or a way to monitor progression or treatment efficacy. miRNA profiling has been employed in a small number of studies in heart [ 159 ] or kidney transplant recipients [ 169 , 171 , 174 , 175 ]. Proposed signatures included several miRNA species overall, while none recurred in different signatures.…”
Section: Liquid Biopsy With the Use Of Sev In Solid Organ And Tissue Transplantationmentioning
confidence: 99%
“…In another study analyzing urinary exosomes, three overexpressed urinary exo-miRs (miR-146b, miR-155, andmiR-200a) in kidney recipients were negatively correlated with TAC dose, while miR-200a was positively correlated with proteinuria [ 174 ]. Investigators were also able to identify significant changes in exosomal cargo corresponding with calcineurin inhibitors toxicity [ 173 ] or eGFR < 60 mL/min/1.73 m 2 [ 175 ]. Candidate biomarkers for different clinical conditions were summarized in Table 1 .…”
Section: Liquid Biopsy With the Use Of Sev In Solid Organ And Tissue Transplantationmentioning
confidence: 99%
“…Many studies show a relationship between exosomal miRNA, which are endogenous NPs, and renal function. Chen et al [ 145 ] aimed to create a circulating exosomal miRNA panel for the non-invasive assessment of renal function after transplantation. The exosomal miRNA panel has advantages, such as non-invasive procedure, miRNA stability and low susceptibility to external factors, and sensitivity in distinguishing chronic graft dysfunction from normal function.…”
Section: Nanoparticles In Diagnosis and Treatment Of Kidney Diseasesmentioning
confidence: 99%